2017
DOI: 10.3390/e19100564
|View full text |Cite
|
Sign up to set email alerts
|

Prior Elicitation, Assessment and Inference with a Dirichlet Prior

Abstract: Methods are developed for eliciting a Dirichlet prior based upon stating bounds on the individual probabilities that hold with high prior probability. This approach to selecting a prior is applied to a contingency table problem where it is demonstrated how to assess the prior with respect to the bias it induces as well as how to check for prior-data conflict. It is shown that the assessment of a hypothesis via relative belief can easily take into account what it means for the falsity of the hypothesis to corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…, x n ) is a sample from the Bernoulli(θ) with θ ∈ [0, 1] unknown so nx ∼ binomial(n, θ) and interest is in θ. For the prior, let θ ∼ beta(α 0 , β 0 ) where the hyperparameters are elicited as in, for example [34], so…”
Section: Example 4 Binomial Proportionmentioning
confidence: 99%
“…, x n ) is a sample from the Bernoulli(θ) with θ ∈ [0, 1] unknown so nx ∼ binomial(n, θ) and interest is in θ. For the prior, let θ ∼ beta(α 0 , β 0 ) where the hyperparameters are elicited as in, for example [34], so…”
Section: Example 4 Binomial Proportionmentioning
confidence: 99%
“…Moreover, P is treated quite differently than other probabilities (see, for example, Evans, Guttman, and Li ( 2017)). Alternative methods are, of course, suggested in the literature (see Zapata-Vázquez, O'Hagan, and Bastos (2014) and Evans et al (2017)) to deal with the elicitation of Dirichlet parameters efficiently but we stick to the method of Dorp and Mazzuchi (2003) simply because of its inherent ease. Moreover, since our illustration in the next section considers a large data size, it is expected that a slight deviation in elicited prior will not affect our final inferences.…”
Section: Subjective Elicitation Of Priormentioning
confidence: 99%
“…Early work focused on representing expert opinion by a Dirichlet distribution, which is the natural conjugate prior distribution for multinomial sampling; reviews of this work may be found in Garthwaite et al (2005) andO'Hagan et al (2006). Modelling opinion by a Dirichlet distribution has continued to attract attention (Zapata-Vázquez et al, 2014;Evans et al, 2017), but methods for eliciting more flexible prior distributions have also been proposed. Elfadaly and Garthwaite (2013) give a method for quantifying expert opinion as both a Dirichlet distribution and a Connor-Mosimann distribution, and give an example to illustrate the greater flexibility of the latter.…”
Section: Introductionmentioning
confidence: 99%